Bipolar coagulation in bipolar electrosprays: Optimizing coagulation efficiency and hetero-agglomerate composition - Kawalek, Matthias; Peukert, Wolfgang; Lübbert, Christian (Journal of Aerosol Science, 2025)
This work investigates the bipolar coagulation of oppositely charged nanoparticles, a few nanometers in size, generated by a bipolar electrospray. These particles form after highly charged droplets produced by the electrospray evaporate, carrying a fraction of the initial droplet charge. The particle charge fraction depends on the non-volatile volume fraction of the feed solution. However, during evaporation, ions and charged clusters form that carry the remaining droplet charge, competing with particle-particle coagulation and thus reducing coagulation efficiency. To enhance coagulation efficiency, the non-volatile volume fraction of the feed solution was increased by adding diethylene glycol (DEG). Additionally, the number of salt particles in the agglomerates was tuned by changing the conductivity ratio of the feed solutions. Experiments were conducted using glucose and sodium chloride particles as a model system for material based applications. Notably, glucose evaporates completely from the coagulated particles, making this system suitable for our tandem DMA setup with a tube furnace between the two DMAs. This setup allowed us to obtain 2D distributions containing information on agglomerate concentration and composition and to optimize coagulation efficiency.
CRIS-Team Scopus Importer:2025-03-28
Keywords: Glucose; Positive ions; Diethylene glycol; Glucose; Sodium chloride; Bipolar coagulation; Charged droplet; Charged nanoparticles; Coagulation efficiency; Electrosprays; Feed solution; Nanometres; Nonvolatile; Particle charge; Particle forms; coagulation; concentration (composition); efficiency measurement; electrokinesis; experimental study; blood clotting; concentration (parameter); conductance; controlled study; electrospray; furnace; Coagulation